Foreign dominations and changes in cretan agriculture: (XIVth-XIXth centuries) - Triantafyllidou-Baladie, Yolande (The Greek Review of Social Research, 1981)
The development and commercialization of the three main products of Cretan agriculture (cereals, vine, olive oil) are seen in relation to the economic policies of the two Powers (first. Venice and then the Ottoman Empirei which successively dominated Crete. The prime objective of these policies was not to act for the interests of Cretan population but for those of the sovereign power. Consequently we can observe that cereal crops and the commer cialization of grain were preponderant at the beginning of Venetian domination; this corresponds to a period when, for various reasons, the Republic badly needed cereals. Venice therefore encouraged these crops until about the end of the XVth century. Then, other factors arise. In the West, industry, expansion of interna tional trade, merchant capitalism, towns are developing,constituting the determining factors for the new agricultural policy adopted by Venice with regard to its colonies; it is the time of monoculture. So that Crete was all assigned to vine cultivation, the fast development of which, during the XVIth century, enabled the island to export im portant quantities of quality wines. It was during this period that Crete expienced its greatest economic progress. However, the international crisis at the end of the XVIth century and Venetians' final loss of the island in the XVIIth century, caused Cretan viticulture to regress. Vine henceforth was to play a secondary part. For a number of reasons due to the economic policy of the Ot toman Empire, we can observe at the same period the development of olive-growing. Olive oil was to become the most important trade in the XVIII th and XIXth centuries.